The Effect of Beauty Influencer, Social Media Marketing, and Brand Image on Purchase Decisions for Korea Skincare Products - Ratna Juwita Permata Nanda; Sengguruh Nilowardono (NAROTAMA UNIVERSITY, Indonesia, 2022)
This study aims to analyze the influence of beauty influencers, social media marketing, brand image on purchasing decisions of Korean skincare products. The analytical method used in this research is quantitative analysis by conducting a survey on 118 respondents, namely Narotama University students who have purchased Korean skincare and tested with the help of an analytical tool, namely the SPSS program. The results of this study indicate that beauty influencers, social media marketing, and brand image have a simultaneous positive effect on Korean skincare purchasing decisions. Partially it only has a significant effect on social media marketing and brand image variables and for the beauty influencer variable it does not have a partially significant effect on purchasing decisions.Beauty Influencer